Les coopérations au développement durable en question dans les pays du Sud - Géraldine Froger (Développement Durable et Territoires)
After identifying decentralized cooperation, its fields of action, changes in its procedures and the ambiguities it faces in supporting sustainable development in developing countries, we focus on sustainable development policies and programs based on more conventional forms of cooperation. However, the decentralized governance of natural resources and environment promoted by these conventional forms of cooperation is facing many difficulties, particularly in Madagascar. Decentralized cooperation can be complementary but its conditions for success depend, among other things, on the success of decentralization processes in the South.